2020
DOI: 10.1186/s12955-020-01427-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a vision-related activity scale for patients with retinitis pigmentosa

Abstract: Purpose: There have been few systematic reports of vision-related activity limitations of people with retinitis pigmentosa (RP). We report a merging of data from the National Eye Institute Visual Function Questionnaire (NEI-VFQ) obtained in five previous studies. We asked whether the Vision Function Scale (VFS; Pesudovs et al., 2010) which was developed for cataract patients would apply in this new population (condition). Methods: Five hundred ninety-four individuals completed a total of 1753 questionnaires, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…One study observed that, compared with the wider RP population, people with XLRP had lower perceived vision-related ability (as assessed with a modified version of the Vision Function Scale). 38 The correlation between reducing visual function and increasing levels of depression in RP supports the hypothesis that humanistic burden can reasonably be expected to be greater for XLRP than for other forms of RP. 29 An increase in patient burden with increasing severity of the condition has been observed in RP more generally: a study that stratified patients with RP by visual field and visual acuity found that HRQL and emotional state worsened as patients approached legal blindness (residual visual field diameter below 20° and a visual acuity less than 0.3 [0.5 log minimum angle of resolution]).…”
Section: Resultsmentioning
confidence: 52%
“…One study observed that, compared with the wider RP population, people with XLRP had lower perceived vision-related ability (as assessed with a modified version of the Vision Function Scale). 38 The correlation between reducing visual function and increasing levels of depression in RP supports the hypothesis that humanistic burden can reasonably be expected to be greater for XLRP than for other forms of RP. 29 An increase in patient burden with increasing severity of the condition has been observed in RP more generally: a study that stratified patients with RP by visual field and visual acuity found that HRQL and emotional state worsened as patients approached legal blindness (residual visual field diameter below 20° and a visual acuity less than 0.3 [0.5 log minimum angle of resolution]).…”
Section: Resultsmentioning
confidence: 52%
“…This cannot be captured by BCVA testing alone. In fact, among different measures of visual function, VF size has been shown to be the best predictor of poor mobility in patients with RP [31]. We found that more advanced VF patterns were more frequently seen in genetically solved cases and identified a VFI <53.50% as the optimal cutoff to differentiate solved from unsolved cases (75% sensitivity; 63% specificity).…”
Section: Discussionmentioning
confidence: 71%
“…118,119 The Vision Function Scale-plus (19 items) survey, initially developed for cataract, has also provided promising results in RCD. 120 Recently, the Michigan Retinal Degeneration Questionnaire was also validated as a PRO for patients with IRD, employing 59 items in 7 domains. 121 Whilst there remains no consensus on the most appropriate PRO tools in IRD and whether they need to be disease/genotype specific given the extreme clinical heterogeneity of IRD, they provide clinically meaningful information for both patients and researchers and are an integral assessment to fully evaluate treatment efficacy and calculate costeffectiveness.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%